A Personalistic Appraisal of Maslow’s Needs Theory of Motivation: From “Humanistic” Psychology to Integral Humanism - Acevedo, Alma (Journal of business ethics, 2018)
Abraham Maslow’s needs theory is one of the most influential motivation theories in management and organizational behavior. What are its anthropological and ethical presuppositions? Are they consistent with sound business philosophy and ethics? This paper analyzes and assesses the anthropological and ethical underpinnings of Maslow’s needs theory from a personalistic framework, and concludes that they are flawed. Built on materialistic naturalism, the theory’s “humanistic” claims are subverted by its reductionist, individualistic approach to the human being, which ends up in a needs-based ethics that understands goodness, virtue, and rights in instinctual, subjectivistic, and relativistic terms. Its moral imperative, “Be yourself!,” is either the materialistic fiat of genetic drives or the voluntaristic command of unbridled will. Significant implications for business educators, managers, and organizations are discussed, along with recommendations. Managerial theories and approaches that reduce personality to individuality are inconsistent with proper anthropological and ethical business principles. Adopting those individualistic theories may ultimately undermine organizational effectiveness, and the very essence of business as human activity and of management as human calling. Instead, personalistic anthropology and virtue ethics, rooted in Aristotelian–Thomistic thought, soundly account for properly human nature and the good life. Business educators and practitioners are encouraged to embrace this integral, truly humanistic framework for motivation, and management theory and practice.